ППН движение S-звезд вокруг SGR A* - Гайнутдинов, Р. И. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В данной работе рассмотрены уравнения движения в рамках параметризованного пост-ньютоновского (ППН) формализма для нескольких S-звезд, ближайших к релятивистски компактному объекту Sgr A* в центре Галактики. Parametrized Post-Newtonian (PPN) equations of motion for several S-stars nearest to the Galactic Center compact relativistic object SgrA* are considered. The effect of the orbital periods difference between Newtonian and Post-Newtonian cases is taken into account.
Keywords: Astrophysics; Stars